2012
DOI: 10.1093/mutage/ges032
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory variation in DNA damage using a standard comet assay protocol

Abstract: There are substantial inter-laboratory variations in the levels of DNA damage measured by the comet assay. The aim of this study was to investigate whether adherence to a standard comet assay protocol would reduce inter-laboratory variation in reported values of DNA damage. Fourteen laboratories determined the baseline level of DNA strand breaks (SBs)/alkaline labile sites and formamidopyrimidine DNA glycosylase (FPG)-sensitive sites in coded samples of mononuclear blood cells (MNBCs) from healthy volunteers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…There have been a number of approaches to increase the throughput of the comet assay at the sample work up stage1213141516, but in all of these have represented a departure from the conventional use of microscope slides to support the cell-containing gels, and therefore significant changes in procedure for the laboratories that undertake this assay. Observations from a recent study have indicated that changing a well-established comet assay procedure can be problematic for some laboratories7, and would therefore be best avoided. Furthermore, a departure from the use of microscope slides may also make more difficult to perform certain variants of the comet assay, such as the enzyme-modified ACA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of approaches to increase the throughput of the comet assay at the sample work up stage1213141516, but in all of these have represented a departure from the conventional use of microscope slides to support the cell-containing gels, and therefore significant changes in procedure for the laboratories that undertake this assay. Observations from a recent study have indicated that changing a well-established comet assay procedure can be problematic for some laboratories7, and would therefore be best avoided. Furthermore, a departure from the use of microscope slides may also make more difficult to perform certain variants of the comet assay, such as the enzyme-modified ACA.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there have been some significant attempts to improve inter-laboratory agreement in levels of damage measured, largely driven by the European Comet Assay Validation Group678, and some new applications e.g. the assessment of DNA damage in whole blood9, the actual comet assay protocol has remained largely unchanged since it was originally described by Östling & Johansson10 and Singh et al11.…”
mentioning
confidence: 99%
“…The level of FPG or hOGG1 sensitive sites was calculated as the difference in DNA damage between slides that had been treated with the FPG or hOGG1 enzyme and buffer. We used Ro19-8022 and light exposed monocytic THP-1 cells as reference controls, which has been used as control in comet assay validation trials [2123]. Ro19-8022 was a gift from F. Hoffmann-La Roche (Basel, Switzerland).The levels of SB, FPG- and hOGG1-sensitive sites were 0.51 ± 0.31, 0.77 ± 0.19 and 0.48 ± 0.12 lesions/10 6 base pairs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The conversion of %T to lesions/10 6 bp increased the percentage of total variation explained by the inter-sample/subject variation from 49 to 73% (Johansson et al, 2010). A subsequent ECVAG trial looked into a standard comet assay protocol, but was only partly successful because some laboratories observed no difference in calibration curve samples and obtained negative values of FPG sensitive sites in human PBMCs (Forchhammer et al, 2012). ECVAG also showed that the overall variation of FPG-sensitive sites in the PBMCs could be partitioned into inter-laboratory (56.7%), residual (42.9%), intra-laboratory (0.2%) and inter-subject (0.3%) variation (Ersson et al, 2013).…”
Section: What About the Use Of A Reference Standard?mentioning
confidence: 99%